Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1080/00016480500452582
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal Rosai-Dorfman disease: involvement of eye, nose and trachea

Abstract: Rosai-Dorfman disease (RDD) is a rare non-neoplastic histiocytic proliferative disorder characterized by painless lymphadenopathy. Extranodal lesions frequently occur in the head and neck regions. We report the clinical and histological features of extranodal RDD in a 43-year-old man with a previously unreported combination of multiple gross anterior epibulbar nodules in the right eye, submucosal masses of nasal septum and trachea, and no lymphadenopathy during the 12-year follow-up. The patient underwent opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 2 publications
3
26
0
1
Order By: Relevance
“…3,13,14 Other sites with biopsyproven involvement were as follows: skin, 9,12 eyelid, 9,12 ethmoid sinus, 12 vocal cord, 8 nasal cavity, 10,11 and trachea. 11 Mean age at onset was 35 years, which is higher than overall SMHL (mean, 19.7 years). There was also a striking male predominance (9:1).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…3,13,14 Other sites with biopsyproven involvement were as follows: skin, 9,12 eyelid, 9,12 ethmoid sinus, 12 vocal cord, 8 nasal cavity, 10,11 and trachea. 11 Mean age at onset was 35 years, which is higher than overall SMHL (mean, 19.7 years). There was also a striking male predominance (9:1).…”
Section: Discussionmentioning
confidence: 83%
“…Zimmerman et al 3 published the first case of an epibulbar tumor as a manifestation of RDD and stated that the presence of lymphadenopathy is not essential for the diagnosis. The review of all published cases 3,[8][9][10][11][12][13][14] showed that, whenever there is an epibulbar tumor as a manifestation of RDD, the absence of lymphadenopathy is characteristic. Only 2 of the 9 reported cases presented with lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,64,65 Although these diagnoses are less common, one should be aware of these processes when forming a differential diagnosis of cervical node enlargement.…”
Section: Pathologymentioning
confidence: 99%
“…Proptosis is the commonest symptom, but blurred vision, diplopia, dry eye, and epiphora may all be seen (Foucar et al, 1979). Other ophthalmological manifestations include epibulbar masses, marginal corneal infiltrates, and uveitis (Nakashima et al, 2006;Ottaviano et al, 2006).…”
Section: Figure 5 Computed Tomographic Scan Of Case 5 Shows An Inferimentioning
confidence: 99%